The Emerald handbook of public-private partnerships in developing and emerging economies - Leitão, João; Sarmento, Elsa Morais; Aleluia, João (Emerald Publishing Limited, 2017)
The Emerald Handbook of Public-Private Partnerships in Developing and Emerging Economies is a comprehensive resource bringing together leading scholars to analyze some of the key aspects associated with the processes of designing, implementing, operating, and evaluating PPPs in the context of emerging economies. Each contribution discusses ways to ensure PPPs result in the highest value for public money and welfare within the Sustainable Development Goals framework. There are four distinct sections: the first lays the groundwork for a thorough understanding of PPPs in developing and emerging countries; the second explores how to make PPPs work for the poor; the third focuses on public policy, public management practices and entrepreneurship; and the fourth uses practical considerations and case studies to address the implementation and evaluation of PPPs. Individual topics covered include public policy practices and social entrepreneurship; implementation and evaluation of PPPs; empirical analysis of PPP determinants; triggers and determinants to PPP implementation; and guiding principles for PPP sustainability and value for money. With a broad scope and final summary of lessons learned and emerging best practices from a range of case studies, this handbook is a go-to source for researchers and students.- Resumé vydavatel
Obsahuje index.
Keywords: veřejně-soukromá partnerství -- rozvojové země; sociální podniky -- rozvojové země; public-private partnerships -- developing countries; social enterprises -- developing countries; sborníky; elektronické knihy; papers of several authors; electronic books